A Novel Star Like Eight-Arm Polyethylene Glycol-Deferoxamine Conjugate for Iron Overload Therapy - Bohong Yu; Yinxian Yang; Qi Liu; Aiyan Zhan; Yang Yang; Hongzhuo Liu (MDPI AG, 2020)
The traditional iron chelator deferoxamine (DFO) has been widely used in the treatment of iron overload disease. However, DFO has congenital disadvantages, including a very short circular time and non-negligible toxicity. Herein, we designed a novel multi-arm conjugate for prolonging DFO duration in vivo and reducing cytotoxicity. The star-like 8-arm-polyethylene glycol (8-arm-PEG) was used as the macromolecular scaffold, and DFO molecules were bound to the terminals of the PEG branches via amide bonds. The conjugates displayed comparable iron binding ability to the free DFO. Furthermore, these macromolecule conjugates could significantly reduce the cytotoxicity of the free DFO, and showed satisfactory iron clearance capability in the iron overloaded macrophage RAW 246.7. The plasma half-life of the 8-arm-PEG-DFO conjugate was about 190 times than that of DFO when applied to an intravenously administered rat model. In conclusion, research indicated that these star-like PEG-based conjugates could be promising candidates as long circulating, less toxic iron chelators.